1987
DOI: 10.1007/bf01644137
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative microbiological analysis of sputa of 102 patients with cystic fibrosis

Abstract: A microbiological analysis of 102 patients suffering from cystic fibrosis was conducted over a 22 month period. 20 microbial species with the following incidence were identified: Pseudomonas aeruginosa: 83.4%; Candida albicans: 29.4%; Staphylococcus aureus: 24.5%; Staphylococcus epidermidis: 11.8%; Haemophilus influenzae: 11.8%; Streptococcus pneumoniae; 6.9%; Pseudomonas maltophilia: 6.8%; Aspergillus fumigatus: 5.9%. Other species were present in less than 5% of the patients. In the majority of specimens wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
120
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 21 publications
5
120
0
2
Order By: Relevance
“…An in-depth understanding of these interactions could be exploited for the benefit of mankind. Pseudomonas and Candida are organisms that are commonly isolated from the sputum of cystic fibrosis patients (Hughes and Kim, 1973;Bauernfeind et al, 1987;Bakare et al, 2003). Both species are common nonpathogenic commensals of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth understanding of these interactions could be exploited for the benefit of mankind. Pseudomonas and Candida are organisms that are commonly isolated from the sputum of cystic fibrosis patients (Hughes and Kim, 1973;Bauernfeind et al, 1987;Bakare et al, 2003). Both species are common nonpathogenic commensals of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Both morphological forms are important for virulence, and the ability to undergo morphological transformation is therefore an important virulence trait (Gow, 1997;Calderone and Fonzi, 2001;Gow et al, 2002;Liu, 2002;Whiteway and Oberholzer, 2004). Several studies have suggested that P. aeruginosa may inhibit C. albicans growth within the host (Bauernfeind et al, 1987;Kerr, 1994;Burns et al, 1999;Gupta et al, 2005;Kaleli et al, 2007). Hogan and Kolter (2002) demonstrated that P. aeruginosa is cytotoxic to the filamentous form of C. albicans but is unable to attach to or kill C. albicans yeast cells.…”
Section: Introductionmentioning
confidence: 99%
“…infections and is often implicated in early infectious airway disease in cystic fibrosis patients (2,5,6,22). S. aureus expresses several potential virulence factors (VF) that may induce airway epithelial injury, inactivate host defense mechanisms, and impair the epithelial wound/repair process.…”
mentioning
confidence: 99%
“…Alpha-toxin, one of the major soluble VF of S. aureus, is able to induce transient apoptosis followed by the necrosis of human airway epithelial cells (HAEC) (9). We have also recently shown that live S. aureus and more predominantly soluble VF in contact with HAEC induce marked alterations in the transcriptional expression profile of HAEC associated with activation of the NF-B and activator protein (AP)-1 pathway, upregulation of PGE 2 and cyclooxygenase (COX)-2 expression and proinflammatory cytokine release such as IL-1␤ and IL-8 (23). The role of the airway inflammation in the pathogenesis of chronic obstructive pulmonary diseases is well known, but the specific effects of S. aureus VF on the regulation of the inflammation have not been well defined.…”
mentioning
confidence: 99%
“…7,8 This pneumococcal colonization has been documented to be transient in CF patients even in the absence of antibiotic therapy. 9,10 CF patients may have an attenuated antibody response to pneumococcus for the following reasons. Many CF patients have been treated, either prophylactically or intermittently, with oral and/or intravenous antibiotics, which usually cover S pneumoniae.…”
mentioning
confidence: 99%